2003
DOI: 10.1038/sj.onc.1207127
|View full text |Cite
|
Sign up to set email alerts
|

Maspin – the most commonly-expressed gene of the 18q21.3 serpin cluster in lung cancer – is strongly expressed in preneoplastic bronchial lesions

Abstract: Maspin, SCCA1/2 and hurpin were identified by cDNA microarray analyses as dramatically differentially expressed transcripts in primary non-small cell lung cancer (NSCLC). These sequences are located within a 10-gene serpin cluster on 18q21.3. Using comparative RT-PCR, we have investigated the expression of each of these serpins, including their flanking loci, in an independent NSCLC series. Whereas six of the genes (maspin, SCCA1, SCCA2, hurpin, megsin and pAI-2) were commonly differentially expressed in prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
71
1
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 41 publications
11
71
1
3
Order By: Relevance
“…Consistent with this finding, tissue microarray analyses have shown that Maspin expression is down-regulated in cancers with a high histological grade and low expression correlates with presence of p53 mutations in various tumor types (34). Interestingly, Maspin is overexpressed in lung cancer, suggesting it may have a role other than tumor suppressor (35). p63, a homolog of p53, transactivates the Maspin promoter via directly binding to the p53 site in cancer cells (15).…”
Section: Discussionsupporting
confidence: 54%
“…Consistent with this finding, tissue microarray analyses have shown that Maspin expression is down-regulated in cancers with a high histological grade and low expression correlates with presence of p53 mutations in various tumor types (34). Interestingly, Maspin is overexpressed in lung cancer, suggesting it may have a role other than tumor suppressor (35). p63, a homolog of p53, transactivates the Maspin promoter via directly binding to the p53 site in cancer cells (15).…”
Section: Discussionsupporting
confidence: 54%
“…These two subtypes may be delineated by TTF (thyroid transcription factor)-1 expression, which is a lineage marker for peripheral airway cells, including type I and II pneumocytes (Yatabe et al, 2004). Interestingly, TTF-1 expression in adenocarcinoma is inversely correlated with expression of maspin (Kobayashi et al, 2004), which we have previously shown to be tightly restricted to basal cells of the bronchial epithelium in normal lung (Smith et al, 2003). Normal alveoli do not express S100A2.…”
Section: Discussionmentioning
confidence: 88%
“…Comparative multiplex (cm) RT -PCR was used to compare levels of test gene transcripts between normal lung and tumour samples, as described previously (Heighway et al, 2002;Smith et al, 2003). Briefly, the test gene transcript was coamplified with a nondifferentially expressed control transcript (APPBP2 -KIAA0228) in the same reaction.…”
Section: Comparative Multiplex Rt -Pcrmentioning
confidence: 99%
“…It is active in cell transition, invasion and metastasis (7). maspin is largely an intracellular protein that is soluble in the cytoplasm and is also found in association with secretory vesicles (45).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid tumors generally express TTF-1 diffusely while immunoreactivity in lung carcinomas is particularly high in SCLCs and ACs in contrast (6). maspin, one of the serine protease inhibitor proteins, leads to reduction in cell permeability, invasion and metastasis (7). It is more commonly expressed in SCCs than in other lung tumors (8).…”
Section: Introductionmentioning
confidence: 99%